Analysis of the Implementation of the Use of Health Center Health Operational Assistance Funds in North Buton Regency in 2021 - Iswanto; Vetty Yulianty Permanasari; Kurnia Sari; Pujiyanto; Izanuddin; Mira Miranti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the implementation of the use of BOK Puskesmas funds in calling for SPM performance in North Buton Regency. This research is an operational research with a case study design and a qualitative approach. Case studies were conducted at the Kulisusu Health Center, Bonerombo Health Center, and North Wakorumba Health Center, North Buton Regency. The results of the study found that in terms of human resources there were still many who were incomplete and there were still several positions filled by health workers who had no expertise. The completeness of facilities and infrastructure at the puskesmas is also not sufficient as standard facilities for implementing programs in the MSS. Planning for the budget for BOK funds for puskesmas is carried out through the preparation of RUK and RPK, but the budget ceiling is still determined by the central government. The delay in issuing the DPA in the APBD and the slow disbursement carried out by the Puskesmas had an impact on the implementation of program activities at the beginning of the year